2002
DOI: 10.1074/mcp.m200029-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylated C-terminal Repeat Domain-associating Proteins in the Nuclear Proteome Link Transcription to DNA/Chromatin Modification and RNA Processing

Abstract: Using an interaction blot approach to search in the human nuclear proteome, we identified eight novel proteins that bind the hyperphosphorylated C-terminal repeat domain (phosphoCTD) of RNA polymerase II. Unexpectedly, five of the new phosphoCTD-associating proteins (PCAPs) represent either enzymes that act on DNA and chromatin (topoisomerase I, DNA (cytosine-5) methyltransferase 1, poly(ADP-ribose) polymerase-1) or proteins known to bind DNA (heterogeneous nuclear ribonucleoprotein (hnRNP) U/SAF-A, hnRNP D). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 101 publications
(90 reference statements)
2
68
0
1
Order By: Relevance
“…This ionic strength [0.4 M (NH 4 ) 2 SO 4 ] has been shown to be sufficient to extract factors associated with elongating Pol II from yeast (42,43), and we have found that it is also more than sufficient to disengage virtually all mammalian PCAPs from RNA Pol II in a chromatin pellet from HeLa cells (39). The crude extract was centrifuged at 14000g (8000 rpm in a Sorvall SLC-6000 rotor) for 45 min at 4 °C to remove cell debris.…”
Section: (C) Methods 3: P11 Fractionationmentioning
confidence: 82%
See 2 more Smart Citations
“…This ionic strength [0.4 M (NH 4 ) 2 SO 4 ] has been shown to be sufficient to extract factors associated with elongating Pol II from yeast (42,43), and we have found that it is also more than sufficient to disengage virtually all mammalian PCAPs from RNA Pol II in a chromatin pellet from HeLa cells (39). The crude extract was centrifuged at 14000g (8000 rpm in a Sorvall SLC-6000 rotor) for 45 min at 4 °C to remove cell debris.…”
Section: (C) Methods 3: P11 Fractionationmentioning
confidence: 82%
“…For example, fractions 23, 25, and 27 have several bands that are detected by the PCTD probe. The pattern of possible phosphoCTD-interacting proteins does not mirror the profile of proteins eluted from the ion-exchange column (not all lanes have putative PCAPs, and not all proteins in any given lane interact with the probe), arguing against the simple possibility that the PCTD probe acts merely as a polyanion (see also discussion in ref 39 and Figure 5G-J).…”
Section: (A) Methods 1 Andmentioning
confidence: 98%
See 1 more Smart Citation
“…TOP1 is an essential enzyme in mammals 30 , and one of its primary functions during cell growth is to maintain DNA topology by relaxing supercoiled DNA 6 . TOP1 can localize to actively transcribed regions and associate with the RNAPIIo elongation complex in vertebrates 31,32 . Our analysis provides insight into the biological function of the TOP1 K391/K436 SUMO modifications during transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The transition from pausing to elongation is facilitated by the P-TEFb elongation complex, which also mediates efficient elongation (10). P-TEFb consists of two subunits, cyclin T1 and the kinase CDK9, which phosphorylates serine 2 of the CTD, required for productive elongation and the recruitment of complexes involved in mRNA processing (splicing and polyadenylation) (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%